Evolution of Surgery for Adolescent Idiopathic Scoliosis Over 20 Years: Have Outcomes Improved?. Issue 6 (15th March 2018) - Lonner, Baron S.; Ren, Yuan; Yaszay, Burt; Cahill, Patrick J.; Shah, Suken A.; Betz, Randal R.; Samdani, Amer F.; Shufflebarger, Harry L.; Newton, Peter O.
Abstract : Study Design: Retrospective review of a prospective adolescent idiopathic scoliosis (AIS) registry. Objective: To study the evolution of the operative approach, outcomes, and complication rates in AIS surgery over the past 20 years. Summary of Background Data: Surgical techniques in AIS surgery have evolved considerably over the past 20 years. We study the trends in the operative management of AIS over this period and their impact on perioperative outcomes. Methods: A total of 1819 AIS patients (1995–2013) with 2-year F/U were studied. Operative approach, perioperative parameters, major complication rates, and SRS outcomes were assessed. Linear regression was used to assess the trend of changes over 5-year quartiles. Results: Mean age at surgery was 14.6 ± 2.1 years, 80.2% were females, and this remained consistent throughout. Operative time, EBL/level, and LOS decreased over the 20 years ( P  < 0.0001). The use of antifibrinolytic (AF) increased from 6.7% to 68.8% in the past 10 years ( P  < 0.0001). Number of levels fused increased and LIV was more distal (in relation to stable vertebrae) over time in Lenke 1 and 2 curves (levels fused 7.97−9.94, P  < 0.0001 and 9.8−11.0, P =0.0134, respectively). Anterior spinal fusion (ASF) in Lenke 1 curves decreased from 81% in the first quartile to 0% in the last ( P  = 0.0429). ASF for Lenke 5 curves evolved from 78% in the second quartile to 0 in the last. Thoracoplasty performance decreased from 76% to 20.3% ( P  = 0.1632). All screw constructs in PSF cases increased from 0% to 98.4% ( P  = 0.0095). Two-year major complication rates decreased over time (18.7%−5.1%; P  = 0.0173). Increased improvement in SRS scores were observed in pain, image, function, and total domains. Conclusion: Evolution of surgical technique in AIS over the past 20 years has resulted in a cessation of anterior only surgery, increasing use of all screw constructs, less blood loss, greater use of AF, shorter operative times and LOS, lower major complications rates, and greater improvements in SRS scores. Level of Evidence: 2